Importance Performance Analysis Kualitas Pelayanan Kesehatan Klien Rawat Jalan Peserta Jaminan Kesehatan Nasional - Putri Alawiyah; Dian Safriantini (Jurnal Kesehatan, 2020)
Health care usually is focused on first-level health services (Puskesmas) to reduce the cost of health care covered by the BPJS Kesehatan. The quarterly visiting data of Jaminan Kesehatan Nasional (JKN) participants in the Inderalaya Puskesmas show a fluctuating trend. The objective of this study is to analyze the level of attribute towards the quality of health care service to the outpatient covered by JKN in the Inderalaya Puskesmas throughout 2018. This study employs a quantitative descriptive research method using Importance-Performance Analysis (IPA). The sample of this study were 122 JKN participants chosen by accidental sampling in the site. Data gathering was conducted with the questionnaires of expectation and reality consisting of eight quality dimensions and 30 attributes of statements. The overall conformity level in this study is 94.16%. The study found many respondents are dissatisfied with five care namely effectiveness (93.14%), physical/direct evidence (91.93%), reliability (93.86%), responsiveness (93.07%), and insurance (93.24%). Results of the cartesian-diagram analysis suggest that from 30 attributes, there were four attributes in the A quadrant, 12 attributes in the B quadrant, 11 attributes in the C quadrant, and three attributes in the D quadrant.